Eventos climáticos de larga escala afetam a produção da pesca de camarões oceânicos no Sul do Brasil - Neves, Kerolen Rosa das (2020)
Effects of climate change are observed in various parts of the world, including the reduction or abnormal warming of the oceans. This condition can affect the abundance and distribution of species, consequently altering the production of fishing in various places in the world. Based on monthly data from commercial fishing between 2000-2018 (18 years old), this study investigated the temporal variability of catches of two species of shrimp of subantarctic origin (Artemesia longinaris and Pleoticus muelleri) in the Subtropical South Atlantic (States of Rio Grande do Sul and Santa Catarina, Southern Brazil) and their relationship with dominant climatic indices in South America. The Mixed Generalized Additive Models revealed that the temperature had an increasing positive effect on the relative abundance of A. longinaris, with the best catches being explained with values above 22 ° C. An opposite pattern was observed for P. muelleri, the largest catches occurred in cold waters with temperatures below 20 ° C. In addition, A.longinaris was positively influenced, while P.muelleri was negatively influenced by climatic indices associated with hot events, such as: the positive phase of the Southern Atlantic Mode and negative of the Southern Oscillation Index (El Niño). We identified that A. longinaris increased its abundance in years associated with hot El Niño events (2015-2016). In contrast, there was less abundance of P. muelleri in years of intense El Niño. It is possible that fluctuations in the relative abundance of both species in the period 2000-2018 are associated with climatic aspects that may interfere with the life cycle and abundance of the studied shrimp. Our results demonstrate that water temperature is an important modulator of the production of A. longinaris and P. muelleri ocean shrimp. In addition, its effect is not restricted to seasonal variation, but also causes interannual fluctuations in shrimp fishery production. In this context, in a global warming scenario, the distribution and abundance of species will depend on their thermal tolerance. Under these circumstances, the natural abundance of P. muelleri shrimp is likely to be reduced, which should have consequences for the trophic network and the fishing economy in southern Brazil